2023
DOI: 10.3233/jad-221031
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation at CREBBP Is Associated with Cognitive Impairment in a Mexican American Cohort

Abstract: Background: The aging Mexican American (MA) population is the fastest growing ethnic minority group in the US. MAs have a unique metabolic-related risk for Alzheimer’s disease (AD) and mild cognitive impairment (MCI), compared to non-Hispanic whites (NHW). This risk for cognitive impairment (CI) is multifactorial involving genetics, environmental, and lifestyle factors. Changes in environment and lifestyle can alter patterns and even possibly reverse derangement of DNA methylation (a form of epigenetic regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Through bioinformatics analysis, for glioma patients, it can be regarded as a prognostic factor in the future (21). Hypermethylation of CREBBP is reported to be related to cognitive impairment in the Mexican-American population (22). CXCR4, known as CXC chemokine receptor type 4, has a wide range of regulatory functions in the immune system and has been widely studied.…”
Section: Discussionmentioning
confidence: 99%
“…Through bioinformatics analysis, for glioma patients, it can be regarded as a prognostic factor in the future (21). Hypermethylation of CREBBP is reported to be related to cognitive impairment in the Mexican-American population (22). CXCR4, known as CXC chemokine receptor type 4, has a wide range of regulatory functions in the immune system and has been widely studied.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in the literature emphasized that oxidative stress can modulate DNA methylation by oxidizing DNA, increasing TET-mediated hydroxymethylation, and influencing the produce the methyl donor S-adenosylmethionine by interfering with the binding of DNA methyltransferases [ 43 ]. A recent study has shown that hypermethylation at the CREBBP gene is associated with cognitive impairment in 551 participants from Mexican American cohort [ 44 ]. In fact, CREB activation is induced after ROS and is critical for the cell survival of neurons.…”
Section: Discussionmentioning
confidence: 99%